2014
DOI: 10.1002/smll.201400612
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐Responsive Upconversion Nanoparticles Stimulate Neurite Outgrowth in PC12 Cells

Abstract: Nerve regeneration is of diagnostic importance in neuroscience in regards to the treatment of degenerative disease. Owing to the ability to release rare-earth ions and produce ROS during upconversion process, upconversion nanoparticles are first reported for promoting neurite outgrowth. Different charged coating materials which play a critical role in cell attachment, can further lead to different effects on cell differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…These conclusions are in line with other studies where it is shown that the nano-structured scaffolds augment cell-material interactions at different steps, such as initial attachment, differentiation of neuronal lineage, and neuronal phenotype and length [26,27,28,29,30,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. It has also been demonstrated by others that nano-topographical features can act as guidance cues to glia and neuron growth on the surface [27,45,47,50,51,53,54].…”
Section: Resultssupporting
confidence: 92%
“…These conclusions are in line with other studies where it is shown that the nano-structured scaffolds augment cell-material interactions at different steps, such as initial attachment, differentiation of neuronal lineage, and neuronal phenotype and length [26,27,28,29,30,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. It has also been demonstrated by others that nano-topographical features can act as guidance cues to glia and neuron growth on the surface [27,45,47,50,51,53,54].…”
Section: Resultssupporting
confidence: 92%
“…Since lanthanide‐doped upconversion nanoparticles (UCNPs) possess the intrinsic properties of absorbing and converting near‐infrared (NIR) light into high‐energy UV, visible, or NIR irradiation, they have been widely applied in biodetection, nanomedicines, and information security . In our previous studies, UCNPs have been used for on‐demand manipulation of cell behaviors, such as cell capture and release and neurite outgrowth of PC12 cells . Bian et al.…”
Section: Methodsmentioning
confidence: 99%
“…To harness the brain's regenerative capacity in order to promote cognition and ameliorate the loss of neural functions in case of injury or disease has been a priority for people in this domain. There is a great demand for therapeutic strategies to boost nerve cell growth and trigger nerve fiber reconnections . Conventional methods use injection of nerve growth factors (NGF), however quick clearance, short half‐life, and degradation of these NGFs is a setback to the healing process and leads to a reduced effective concentration reaching the damaged nerves …”
Section: Applications Of Msnsmentioning
confidence: 99%